Pengaruh Kepemimpinan, Motivasi, dan Pelatihan Kerja Terhadap Kinerja Karyawan Pada UD. Jaya Abadi Kabupaten Probolinggo - Ivan Ahmad Farisi; Khusnik Hudzafidah; Dedi Joko Hermawan (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research aims to determine the influence of leadership, motivation and job training on employee performance. Quantitative research with causal associative relationships is the type of research used. Leadership (X1), motivation (X2) and job training (X3) are independent variables. Meanwhile, performance (Y) is the dependent variable used in this research. The sample in this research was 35 employees from a total population of 35 employees. The sample used in this research was non-probability sampling with a saturated sampling technique. The results of the research show that the temporary hypothesis test (Hypothesis) (T-Test) that has been carried out can conclude that leadership has an effect on employee performance, motivation has an effect on employee performance and job training has an effect on employee performance.